Behold the land the black arts movement in the South - Smethurst, James (John Hope Franklin Series in African American History and Culture, 2021)
"In the mid-1960s, African American artists and intellectuals formed the Black Arts movement in tandem with the Black Power movement, with creative luminaries like Amiri Baraka, Gwendolyn Brooks, Toni Cade Bambara, and Gil Scott-Heron among their number. In this follow-up to his award-winning history of the movement nationally, James Smethurst investigates the origins, development, maturation, and decline of the vital but under-studied Black Arts movement in the South from the 1960s until the early 1980s"--